Public Pension Promises: How Big Are They and What Are They Worth? - NOVY‐MARX, ROBERT; RAUH, JOSHUA (Journal of Finance, 2011)
ABSTRACT We calculate the present value of state employee pension liabilities using discount rates that reflect the risk of the payments from a taxpayer perspective. If benefits have the same default and recovery characteristics as state general obligation debt, the national total of promised liabilities based on current salary and service is $3.20 trillion. If pensions have higher priority than state debt, the value of liabilities is much larger. Using zero‐coupon Treasury yields, which are default‐free but contain other priced risks, promised liabilities are $4.43 trillion. Liabilities are even larger under broader concepts that account for salary growth and future service.